Burnout and Life Satisfaction among Healthcare Workers Related to the COVID-19 Pandemic (Silesia, Poland) - Daria Łaskawiec-Żuławińska; Mateusz Grajek; Karolina Krupa-Kotara; Patryk Szlacheta; Hasan Karacan; Mateusz Roszak; Beata Łabuz-Roszak; Ilona Korzonek-Szlacheta (Behavioural Neurology, 2024)
Background. The phenomenon of burnout among healthcare workers during the COVID-19 pandemic is a widespread problem with several negative consequences for the healthcare system. The many stressors of the pandemic have led to an increased development of anxiety and depressive disorders in many healthcare workers. In addition, some manifested symptoms of the so-called postpandemic stress syndrome and the emergence of occupational burnout syndrome, commonly referred to as “COVID-19 burnout.” The aim of this study was to assess the burnout and life satisfaction of healthcare workers during the COVID-19 pandemic. Materials and Methods. The study was conducted in 2020-2022 among medical staff working in hospitals in Silesia, Poland. The instruments used to assess life satisfaction and burnout were the Satisfaction with Life Scale (SWLS) and the Maslach Burnout Inventory (MBI), which assesses three dimensions: emotional exhaustion (EE), depersonalisation (DEP), and sense of reduced professional accomplishment (SRPA). Results. The study group included 900 participants. There were 300 physicians (mean age 38±7 years), 300 nurses (mean age 35±6 years), and 300 paramedics (mean age 31±5 years). Life satisfaction as measured by the SWLS was lowest among nurses and paramedics in 2021 and among doctors in 2022. Male respondents and those with fewer years of work had higher levels of life satisfaction. People with more years of work had higher scores in EE and DEP and lower scores in SRPA (p=0.001). We found a negative correlation between life satisfaction and EE (p=0.001), DEP (p=0.001), and SRPA (p=0.002). Conclusions. The results highlight the need for further research into the causes of burnout among medical professionals and the need for effective interventions to promote well-being and prevent burnout in this group.